Pagan Theology Paganism as a World Religion - York, Michael (New York University Press, 2003)
In Pagan Theology, Michael York situates Paganism-one of the fastest-growing spiritual orientations in the West-as a world religion. He provides an introduction to, and expansion of, the concept of Paganism and provides an overview of Paganism's theological perspective and practice. He demonstrates it to be a viable and distinguishable spiritual perspective found around the world today in such forms as Chinese folk religion, Shinto, tribal religions, and neo-Paganism in the West.While adherents to many of these traditions do not use the word "pagan" to describe their beliefs or practices, York contends that there is an identifiable position possessing characteristics and understandings in common for which the label "pagan" is appropriate. After outlining these characteristics, he examines many of the world's major religions to explore religious behaviors in other religions which are not themselves pagan, but which have pagan elements. In the course of examining such behavior, York provides rich and lively descriptions of religions in action, including Buddhism and Hinduism.Pagan Theology claims Paganism's place as a world religion, situating it as a religion, a behavior, and a theology